THE ROLE AND IMPORTANCE OF THE MASS MEDIA IN IMPROVING SOCIETY'S LITERACY ("Conference on Universal Science Research 2023", 2023)
This article talks about the role of the mass media in today's developing era and the role and importance of the mass media in shaping the society's spirituality and political thinking, as well as about the effective reforms that are being implemented in the world and our republic in.